2020
DOI: 10.1002/jcla.23572
|View full text |Cite
|
Sign up to set email alerts
|

Circulating long noncoding RNA, GAS5, as a novel biomarker for patients with atrial fibrillation

Abstract: Background Circulating long noncoding RNA (lncRNA) plays a vital role in clinical disease diagnosis and prognosis. Here, we evaluate the role of a lncRNA, named growth arrest specific 5 (GAS5), in atrial fibrillation (AF). Methods Expression of GAS5 was measured by qRT‐PCR. Diagnostic and prognostic values of GAS5 were assessed by the receiver operating characteristics curve (ROC), Kaplan–Meier (KM) and Cox regression analyses. Results A total of 173 participants were enrolled in this study. Circulating GAS5 e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Additionally, the lncRNA GAS5 was found downregulated in the AF patients, and the change of the GAS5 occurred prior to the left atrial enlargement. Moreover, the GAS5 was negatively correlated to the ALK5, which could enhance the AF progression (143,144). Besides, the lncRNA VDAC2P2, PVT1, NEAT1, PCAT-1, LICPAR, and NRON were increased in the AF patients, which were positively correlated with the collagen production and fibroblasts proliferation (145)(146)(147)(148)(149)(150)(151).…”
Section: Long Non-coding Rnas In Afmentioning
confidence: 99%
“…Additionally, the lncRNA GAS5 was found downregulated in the AF patients, and the change of the GAS5 occurred prior to the left atrial enlargement. Moreover, the GAS5 was negatively correlated to the ALK5, which could enhance the AF progression (143,144). Besides, the lncRNA VDAC2P2, PVT1, NEAT1, PCAT-1, LICPAR, and NRON were increased in the AF patients, which were positively correlated with the collagen production and fibroblasts proliferation (145)(146)(147)(148)(149)(150)(151).…”
Section: Long Non-coding Rnas In Afmentioning
confidence: 99%
“…Shi et al demonstrated that expression of lncRNA GAS5 was down-regulated in AF patients, which occurred before enlargement of the left atrium, indicating that it can be used as an early biomarker of AF. In addition, they also showed that patients with reduced expression of GAS5 have a higher probability of AF recurring after radio-frequency catheter ablation ( 97 ). To be able to predict the risk of stroke in AF patients, Zeng et al monitored AF patients and compared the levels of the lncRNA ANRIL (antisense non-coding RNA in the INK4 locus) in the stroke group and a non-stroke group.…”
Section: Non-coding Rnas In Atrial Fibrillationmentioning
confidence: 99%
“…In terms of the heart, lncRNAs have been shown to be closely related to the occurrence of heart disease (7). For example, lncRNA GAS5 is identified to be downregulated in the serum of AF patients and shows a strong association with the progression and recurrence of AF (8). Another lncRNA LICPAR is also reported to promote the viability and proliferation of AFs and is involved in the progress of AF via modulating TGF-β/Smad pathway (9).…”
Section: Introductionmentioning
confidence: 99%